Answer:
For 1 cup of peanut Kevin will use
of raisins.
Explanation:
Given:
cups of peanuts =
cups of raisin
can be rewritten as
cups of peanuts =
cups of raisin
We need to find number of cups of raisins used in 1 cup of peanut.
Solution:
Now we know that;
cups of peanuts =
cups of raisin
So 1 cup of peanut = number of cups of raisins used in 1 cup of peanut
Now by using Unitary method we get;
number of cups of raisins used in 1 cup of peanut =
Hence For 1 cup of peanut Kevin will use
of raisins.